دور معايير المحاسبة الدولية في القطاع العام ( IPSAS ) في تفعيل أداء المؤسسات الاقتصادية والأجهزة الحكومية: بحث تطبيقي في محافظة ذي قار (Journal of Accounting and Financial Studies ( JAFS ), 2020)
One of the most distinguished instrumentsis being used by the state for implementing its strategy andachieving perfectly and effectively its goals and policies, and economizing the Public Finance and uplifting the services level for the sake of people, is truly thegovernmental accounting system. Thus, through this system the upper hand is located for supplying the accurate information, which does make the complete and just expressing concerning the budget implementing results. So,this research comes here because of the hugeness in this sector and the associations largeness and the dread of the governments failure in fulfilling its obligations and the provided services, and the required need for the effective and capable informing and the lack to bring on improvements to the administrating of the general sector resources.Also, this research is done here as the accountants international union has realizedthe need of some unified international fromgeneral sector in accounting, just to improve the credibility in the quality and trustworthy in the governmental financial data and reports.Therefore, this study is presented to unveiling of thegovernmental effective units’reality, and auditing of the effectiveness scope and its quality in using the provided economic resources. This research has confronted two following problems here: (( the governmental accounting system, applied in the central financing units, supply enough information for audit and supervising doing and valuate performance ،  and the international accounting criterion adopted No (1) going to lead of providing financial reports satisfy the information users’ needs. Thus, this leads to activate the governmental audit to the economic associations and the governmental offices. ))This study is based onhypotheses stated as the following: (( Will the international accounting criterion needs in the general sector,be relied on and implemented( financial data revelations) concerning of givingand showing up financial lists according to valuated base lead to supplying information users’ needs and governmental financial reports)) .under the light of what has been mentioned, this study will open the road to: (( To develop the financial reports on the Iraqi governmental accounting system, then increasing the advantage of this information provided to the users through the international governmental accounting criterion No(1) which suites the Iraqi environment.))One of the most important conclusions I have reached to is1- Using the accounting merit as a base to record the financial deals has a great role in knowing the results of the governmental units' activity. This will be done by adopting international accounting criteria in the public sector.2-The aims of the governmental financial reports, which have been set according to the IPSAS criteria requirements ,do satisfy the needs and requirements of the governmental financial users which help them to audit and correct the performance of the economic units and governmental associations.The most distinguished recommendations are the following:-1Working on to change and fix the accounting methods and practices adopted in the governmental units in a way which suits the international directions in the field of using criteria as a base to the governmental units and meets with the Iraqi environment.-2Working on copy the developments in the international accounting criteria field in the republic sector due to the advantages, which help in case of adopting, to audit the governmental units and correct its performance through adopting these criteria